Fault-controlled upwelling of low-T hydrothermal fluids tracked by travertines in a fold-and-thrust belt, Monte Alpi, southern apennines, Italy. (March 2021) - Smeraglia, L.; Giuffrida, A.; Grimaldi, S.; Pullen, A.; La Bruna, V.; Billi, A.; Agosta, F.
Abstract: Active faults within the southern Apennines fold-and-thrust belt modulate the present-day upwelling of hydrothermal fluids at surface. In the Monte Alpi area, we investigated the structural and geo-morphological settings of a 10 km 2 -wide area, and texture and stable isotope composition of Quaternary travertine deposits to identify the present day fault-controlled pathways of low-T hydrothermal fluids at shallow crustal depths. Results of 1:10, 000 geological mapping and microstructural analyses show that the Monte Alpi travertines were deposited in a paleo-fluvial environment consisting of cascades and pool/barrage systems, including shallow caves. Travertines precipitated from CO2 -rich meteoric-derived paleo-fluids that yielded δ 18 O compositions from −7.7‰ to −10.1‰. Values in this range overlap the δ 18 O values of water from active hydrothermal springs in the study area. Accordingly, we assess that travertines precipitated from fluids similar to those currently emerging from low-T ( 22 °C) hydrothermal springs active in the study area. In particular, the SO4 chemical signature of hydrothermal springs indicates a complex circulation implying: (1) the infiltration at depth of original meteoric fluid into the Monte Alpi carbonate massif; (2) fluid warming by the geothermal gradient, CO2 enrichment, and interaction with the local stratigraphy (Messinian sulphate-rich deposits); and (3) fluid upwelling through highly permeable fault zone compartments that correspond to fault intersections. Structural analysis and aerial photo interpretation show that sub-parallel fault scarps and landslide escarpments controlled the depositional setting of the travertines. Moreover, travertines only occur above carbonates rocks, whereas travertines are virtually absent along fault scarps and landslide escarpments in shales and metapelites. We conclude that, at fault intersections, high-permability fluid conduits localize along fault zones that sub-parallel the current σhmax of the southern Apennines. In contrast, we infer that clay smearing along fault segment that cut shales and metapelites resulted in low-permeability fault zones, which hampered fluid upwelling. Highlights: Low-T (22 °C) hydrothermal fluids originate from meteoric waters warmed at depth. Hydrothermal fluids feed springs with constant flow rates and temperatures. Hydrothermal fluid precipitate travertines in cascades, pools, barrages, and caves. Fluids channelled at depth within a fault zone oriented sub-parallels to σhmax . Clay smearing along faults in marls and shales hindered hydrothermal fluids upwelling.